Comparison of sport tourists' and locals' motivation to participate in a running event. Issue 3 (19th October 2015) - Aicher, Thomas J.; Karadakis, Kostas; Eddosary, Melfy M
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is two-fold. First, the authors compared tourists with local participants to determine if motivations to participate in a mid-scale marathon event varied based on participant type, and if they perceived the event differently. Second, Kaplanidou and Vogt suggested further testing and validation of their scale to measure meanings people attach to sport events was warranted, and the current investigation provides such evaluation. Design/methodology/approach – Working with the event organizer, the authors distributed an online questionnaire to marathon participants in a mid-scale event. The questionnaire included the Sport Motivation Scale-II, Sport Event Evaluation Scale, and demographics. Findings – Results indicated no differences between sport tourists and residents in motivation and meanings attached to the event; however, differences in perception did exist. Data further validated the Sport Event Evaluation Scale. Research limitations/implications – The study established self-determination theory (SDT) as a viable theoretical framework to understand sport event participants motivations. It demonstrated a possible link between the individuals' motivations and the meanings they associate with the event. Practical implications – The paper provides data to support marketing the healthy benefits of participating in a marathon event as well as the need to include the fun and entertaining components of the event as well. Originality/value – The study is a unique application of SDT as well as applies a theoretical framework to an area of study that has largely focussed on categorizations. Additionally, the findings establish initial findings that local participants and sport tourists possess similar forms of motivation and attach similar meanings to event participation.